A comparative study on enhancing oil recovery with partially hydrolyzed polyacrylamide: Emulsion versus powder. (20th September 2021) - Han, Xu; Li, Changqing; Pan, Feng; Li, Yuxi; Feng, Yujun
Abstract: In China, powders of partially hydrolyzed polyacrylamide (P‐HPAM) have been extensively used in chemically enhanced oil recovery (cEOR) processes. However, the relatively longer dissolution time of P‐HPAM and high investment in surface facilities diminish the profit. Here, we compared the properties between P‐HPAM and emulsion HPAM (E‐HPAM) with similar molecular weight of 1.5 × 10 7 g/mol at polymer concentration of 1000 mg/L under a simulated Daqing Oilfield reservoir. We found only 20 min was needed to completely dissolve E‐HPAM, 75% less time than for P‐HPAM. The apparent viscosity of E‐HPAM reached 69.6 mPa · s, 26% higher than that of P‐HPAM. Sheared at 7000 rpm for 30 s, 73.8% viscosity retention was maintained for E‐HPAM solution, 13.7% higher than that of P‐HPAM solution. After 90 days of thermal aging, E‐HPAM solution had 72.8% viscosity retention, 15.2% higher than P‐HPAM. After being adsorbed in a sand package, E‐HPAM and P‐HPAM solutions had 87.0% and 83.2% viscosity retention, respectively. The interfacial tension (IFT) between E‐HPAM solution and Daqing oil could reach 15.3 mN/m, 75.1% lower than that of the P‐HPAM solution with Daqing oil. After 1.2 PV of polymer solution was injected, E‐HPAM solution got an oil recovery factor of 24.1% (OOIP), 10.0% higher than that of P‐HPAM under identical conditions. Both polymer solutions could propagate smoothly in porous media without plugging. In the field trial of 63 wells, after 0.098 PV of E‐HPAM solution was injected within nine months, the injection pressure increased by 1.3 MPa, and an interim recovery factor of 0.58% was obtained.